Characterization of vegetation cover and proposed ecological connectivity network in the Volcánica Central-Talamanca Biological Corridor, Costa Rica - Murrieta Arévalo, Eduardo (2006)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2006